(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The leadership of the head of the madrasah is said to be successful if the activities that are part of the madrasah program can be carried out properly and in accordance with expectations. As well as how the head of the madrasa is able to encourage its members to carry out their duties and responsibilities together. Based on this, the purpose of this study is the leadership of the head of the madrasa in developing a religious culture in Madrasah Aliyah Bahrul Ulum Tambak Beras Jombang. The objectives of this study include: to determine the role of the head of the madrasah, to determine the strategy of the head of the madrasah, and the implications of the development of religious culture in Madrasah Aliyah Bahrul Ulum Tambak Beras Jombang. This can be proven by the role of madrasah principals and teachers in developing religious culture for students to become useful graduates in society.